The Role of Adaptive Physical Education in Improving Quality of Life for Disabled Individuals - Muhammad Sakib Sad Siddiqui; Harish Kumar (Recent Trends in Sports, 2025)
The purpose of this paper is to analyze the effectiveness of Adaptive Physical Education (APE) in enhancing the quality of life of disabled students at Punjabi University, Patiala. APE refers to an interface that is mainly aimed at the person with disabilities’ physical and psychological characteristics, which enable the original physical activities to be adapted to the disabled person's nature and rounded by conductive physical health examinations, fitness tests, and adaptive measures to assess the impact of APE. Through tailored physical activities, APE enhances motor skills, physical fitness, and functional independence, thereby reducing secondary health complications commonly associated with disabilities. The inclusive nature of APE also facilitates social integration and reduces stigmatization, providing disabled individuals with greater opportunities for participation in community and recreational activities. Moreover, participation in adaptive physical education fosters self-esteem, confidence, and social interaction, which are crucial for psychological well-being. The study affirms that APE physiologically raises the physical well-being, flexibility, and social interaction among students with disability. Special emphasis is placed on the individual approaches to exercise and education that are crucial in increasing the participants’ health and self-esteem. Nevertheless, the research discusses several gaps that hinder the successful incorporation and practice of APE: Both educators and healthcare departments lack awareness of APE and appropriate infrastructures that can support it; society entails prejudice towards people with disabilities. This paper raises a voice for policy change and institutional support for APE’s development in the future of Indian universities, as well as other schools, colleges, so that disabled students, including those of Punjabi University, Patiala, get the opportunity to change their lives and improve their conditions in the future.
Keywords: Adaptive Physical Education (APE); Disability Inclusion; Employment Opportunities; Physical Fitness; Punjabi University; Rights of Disabled Individuals; Social Integration; higher education